Nanotechnology in Eco-efficient Construction : Materials, Processes and Applications - Torgal, Fernando Pacheco; Diamanti, Maria Vittoria; Nazari, Ali; Goran-Granqvist, Claes; Pruna, Alina; Amirkhanian, Serji (Woodhead Publishing series in civil and structural engineering., 2019)
Covering the latest technologies, Nanotechnology in eco-efficient construction provides an authoritative guide to the role of nanotechnology in the development of eco-efficient construction materials and sustainable construction. The book contains a special focus on applications concerning concrete and cement, as nanotechnology is driving significant development in concrete technologies. The new edition has 14 new chapters, including 3 new parts: Mortars and concrete related applications; Applications for pavements and other structural materials; and Toxicity, safety handling and environmental impacts. Civil engineers requiring an understanding of eco-efficient construction materials, as well as researchers and architects within any field of nanotechnology, eco-efficient materials or the construction industry will find this updated reference to be highly valuable.